2013
DOI: 10.3892/or.2013.2283
|View full text |Cite
|
Sign up to set email alerts
|

Poly(amido amine) is an ideal carrier of miR-7 for enhancing gene silencing effects on the EGFR pathway in U251 glioma cells

Abstract: microRNAs are regarded as promising drugs for glioma gene therapy. However, conventional administration routes, such as oral administration and intravenous infusion, present low efficiency due to the blood-brain barrier and intercellular retention, thereby limiting their application. Recent studies showed poly(amido amine) (PAMAM) was a candidate carrier due to its high solubilization, delayed release and low toxicity. In the present study, U251 human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…Cui et al, , X. Cui et al, ; Da Ros, Gutierrez‐Perez, Ferres‐Marco, & Dominguez, ; Feng et al, ; Higuchi et al, ; Horsham et al, ; Hua et al, ; Huynh & Jones, ). In addition, miR‐7‐5p was reported to exert a tumor‐suppressive function in glioblastoma and glioma by regulation of the EGFR, PI3K/ATK, Raf/MEK/ERK, and IGF‐1R pathways (X. Liu et al, , M. Liu et al, ; W. Wang et al, , B. Wang et al, ). Regulation of miR‐7 by circular RNAs, such as ciRS‐7, has been found as a critical approach to advance our interpretation of numerous tumor etiologies (Hansen, Kjems, & Damgaard, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al, , X. Cui et al, ; Da Ros, Gutierrez‐Perez, Ferres‐Marco, & Dominguez, ; Feng et al, ; Higuchi et al, ; Horsham et al, ; Hua et al, ; Huynh & Jones, ). In addition, miR‐7‐5p was reported to exert a tumor‐suppressive function in glioblastoma and glioma by regulation of the EGFR, PI3K/ATK, Raf/MEK/ERK, and IGF‐1R pathways (X. Liu et al, , M. Liu et al, ; W. Wang et al, , B. Wang et al, ). Regulation of miR‐7 by circular RNAs, such as ciRS‐7, has been found as a critical approach to advance our interpretation of numerous tumor etiologies (Hansen, Kjems, & Damgaard, ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous ligands have been attached to dendrimers, including PEG, transferrin, tamoxifen, rabies virus glycoprotein and angiopep-2, to name a few [61][62][63][64]. These ligands prolong circulation time, reduce immuno genicity, improve BBB bypass, aide in cell targeting and balance particle charge.…”
Section: • • Preclinical Studies: Systemic Deliverymentioning
confidence: 99%
“…Poly(amido amine) (PAMAM) has been found to be an effective carrier for the delivery of miR-7 into glioma cells owing to its low toxicity, high solubilization, and delayed release [49]. A recent study demonstrated the successful delivery of tumor suppressor miRNA (let-7a)-conjugated magnetic NPs to brain cells followed by magnetic hyperthermia.…”
Section: Using Nanotechnology Formulations To Deliver Mirnas To Tumorsmentioning
confidence: 99%